PROTEIN-PROTEIN INTERACTION ANALYSIS TO IDENTIFY NEW DRUG TARGETS FOR DIABETES - Savitri, Dita Nurul; Syauqi, Anis; Naibaho, Netty Maria; Muntasir, Muntasir (Yayasan Adra Karima Hubbi, 2025)
The background of this study focuses on diabetes, a chronic metabolic disease characterized by impaired glucose and insulin regulation. Although existing therapies are available, insulin resistance and other complications remain a major challenge. The purpose of this study is to identify new drug targets through the analysis of protein interactions that play a role in the pathogenesis of diabetes. The method used is protein interaction network analysis (PPI) using public databases such as STRING and BioGRID to map the interaction between proteins related to glucose metabolism and insulin. The results of this study identified more than 150 proteins that interact with each other in the regulatory pathways of glucose and insulin metabolism, with several new proteins found to have the potential to be drug targets to overcome insulin resistance. The study concludes that a protein interaction-based approach can open up opportunities to develop new therapies that are more specific and effective in managing diabetes. Further development should be undertaken for the validation of these findings in animal models and clinical trials to confirm their effectiveness as a diabetes therapy.